Low level perceptual, not attentional, processes modulate distractor interference in high perceptual load displays: evidence from neglect/extinction - Mevorach, Carmel; Tsal, Yehoshua; Humphreys, Glyn (Frontiers in Psychology, 2014)
According to perceptual load theory (Lavie, 2005) distractor interference is determined by the availability of attentional resources. If target processing does not exhaust resources (with low perceptual load) distractor processing will take place resulting in interference with a primary task; however when target processing uses-up attentional capacity (with high perceptual load) interference can be avoided. An alternative account (Tsal & Benoni, 2010) suggests that perceptual load effects can be based on distractor dilution by the mere presence of additional neutral items in high load displays so that the effect is not driven by the amount of attention resources required for target processing. Here we tested whether patients with unilateral neglect or extinction would show dilution effects from neutral items in their contralesional (neglected/extinguished) field, even though these items do not impose increased perceptual load on the target and at the same time attract reduced attentional resources compared to stimuli in the ipsilesional field. Thus, such items do not affect the amount of attention resources available for distractor processing. We found that contralesional neutral elements can eliminate distractor interference as strongly as centrally presented ones in neglect/extinction patients, despite contralesional items being less well attended. The data are consistent with an account in terms of perceptual dilution of distracters rather than available resources for distractor processing. We conclude that distractor dilution can underlie the elimination of distractor interference in visual displays.